Práticas pedagógicas transgressoras: possibilidades para uma educação antirracista a partir do prêmio Educar para a Igualdade Racial (CEERT) - Andrade, Maíra Pires (2022)
Education emerges in the historical trajectory of the black movement in Brazil as a fundamental element for the transformation of racial relations, the fight against racism and inequality. The introduction of African and Afro-Brazilian history, as well as the education of ethnic-racial relations, is an old agenda of many black movements established in Brazil, although it only became mandatory with the sanction of Law 10.639/03. After 19 years of this law, its implementation, according to several studies, still brings challenges and obstacles to be overcome. On the opposite side of this panorama of difficulties, since 2002 there has been the constitution of a reference collection of successful anti-racist pedagogical practices in the school environment: the practices of the prize Educar para a Igualdade Racial (“Educating for Racial Equality"), organized by the Center for the Study of Labor Relations and Inequalities (CEERT). The first edition of the Prize was in 2002 and the last, so far, in 2015. That said, this research’s thesis is the existence, among recurrent difficulties and absences in the effectiveness of anti-racist practices, the constitution of a collection of reference practices for the Prize, which enable us to put together strategic axes for the implementation of anti-racist education. The objective is to demonstrate that, despite the continuities and absences in the school space, there are pedagogical practices seen as transgressive and important emergencies that decenter the eurocentric and racist narratives in the classroom. Those must be strengthened and made visible. The first chapter addresses the creation of CEERT as an active institution in the anti-racist field and its connections with the trajectory of the Brazilian black movement. In the second chapter, the objective is understanding the process of constitution and structure of the Prize, from the performance of the reviewers, the selection criteria, to the changes in the notice and the Prize. The third and fourth chapters focus on the analysis of the Prize's pedagogical practices and the identification of knowledge of the black movement in the form of strategic axes, with the aim of, in the end, listing effective possibilities for an anti-racist education